Tilapia Agribusiness Development Strategy at Rahmat Fish Farm to Increase Income and Business Sustainability - Muh Faturokhman; Warchito; Ayutyas Sayekti; Faisal Ali; Fauzia Noorchaliza (Jurnal Manajemen dan Organisasi, 2026)
The increasing demand for fisheries commodities following the implementation of the Free Nutritious Meal (MBG) program presented both opportunities and challenges for tilapia agribusiness actors. Rahmat Fish Farm, a medium-scale enterprise in Bandung, faced managerial and technical constraints that led to supply-demand imbalance and suboptimal operational efficiency. This study aimed to formulate adaptive and sustainable development strategies for tilapia agribusiness. A descriptive approach was employed using Internal Factor Evaluation (IFE), SWOT Matrix, and Quantitative Strategic Planning Matrix (QSPM). Data were collected through field observations, in-depth interviews, and literature review. The results of the IFE analysis indicated that the company was positioned in the “Hold and Maintain” strategic quadrant. SWOT analysis generated alternative strategies focusing on strengthening internal management and partnership development. Based on the QSPM results, five priority strategies were identified: (1) improving inventory management, (2) opening a new branch in Pangalengan, (3) evaluating partner satisfaction, (4) enhancing partner capacity through training and mentoring, and (5) strengthening internal human resources. These findings provided strategic recommendations to support the sustainability of tilapia agribusiness operations.